PENGARUH MEDIA ADVERTISING ABOVE THE LINE TERHADAP KEPUTUSAN MENGINAP DI ASTON BRAGA HOTEL AND RESIDENCE BANDUNG (Survei Pada Free Individual Traveller yang Menginap di Aston Braga Hotel And Residence Bandung) - Juwitasari, Amalia; Siswhara, Gita (Universitas Pendidikan Indonesia, 2015)
As time goes by, the tourism sector in Indonesia has grown and developed into an independent industry sources. National tourism develeopment has the purpose of facilitating the national tourism business, as one source of foreign countries, and the need to improve the organization and functioning of the implementing body in the field of tourism. Hotel industry is an important industry in tourism activities because hotel industry gives a large contribution for tourism sector. Aston Braga Hotel and Residence Bandung as one of four stars hotel in Bandung always strive to maintain aand increase every important aspects which are related to the main goal that is get customer loyalty. The goal can be reached by giving the best services to the guest that greatly exceeds their ecpectations and give an expectional experiences which hard to find in other hotels. In this research, independent variable (X) that used is media advertising above the line which is television, magazine, internet, dan billboard. Dependen variable (Y) is free individual traveller decisison to stay. This type of research is descriptive verification , and the method used sytematic random sampling tehnique, the number of sample obtained for 100 guest who stay Aston Braga Hotel and Residence Bandung. tehniques of data analysis and hypothesis testing used path analysis. The results showed that media advertising above the line significantly influence in decision to stay. The most influential factors for the media advertising above the line is internet which one most higher in reached decision to stay.